Dietary Patterns Are Associated with Predicted 10-Year Risk of Cardiovascular Disease Among Ghanaian Populations: the Research on Obesity and Diabetes in African Migrants (RODAM) Study. Issue 5 (24th April 2019) - Boateng, Daniel; Galbete, Cecilia; Nicolaou, Mary; Meeks, Karlijn; Beune, Erik; Smeeth, Liam; Osei-Kwasi, Hibbah Araba; Bahendeka, Silver; Agyei-Baffour, Peter; Mockenhaupt, Frank P; Spranger, Joachim; Grobbee, Diederick E; et al.
ABSTRACT: Background: Sub-Saharan African populations are disproportionately affected by cardiovascular disease (CVD). Although diet is an important lifestyle factor associated with CVD, evidence on the relation between dietary patterns (DPs) and CVD risk among sub-Saharan African populations is limited. Objective: We assessed the associations of DPs with estimated 10-y atherosclerotic cardiovascular disease (ASCVD) risk in Ghanaian adults in Ghana and Europe. Methods: Three DPs ('mixed'; 'rice, pasta, meat, and fish'; and 'roots, tubers, and plantain') were derived by principal component analysis (PCA) based on intake frequencies obtained by a self-administered Food Propensity Questionnaire in the multi-center, cross-sectional RODAM (Research on Obesity and Diabetes among African Migrants) study. The 10-y ASCVD risk was estimated using the Pooled Cohort Equations (PCE) for 2976 subjects, aged 40–70 y; a risk score ≥7.5% was defined as 'elevated' ASCVD risk. The associations of DPs with 10-y ASCVD risk were determined using Poisson regression with robust variance. Results: Stronger adherence to a 'mixed' DP was associated with a lower predicted 10-y ASCVD in urban and rural Ghana and a higher 10-y ASCVD in Europe. The observed associations were attenuated after adjustment for possible confounders with the exception of urban Ghana (prevalence ratio [PR] for Quintile 5 compared with 1: 0.70; 95% CI: 0.53, 0.93, P -trend = 0.013). The 'rice, pasta, meat, and fish' DP was inversely associated with 10-y ASCVD across all study sites, with the adjusted effect being significant only in urban Ghana. A 'roots, tubers, and plantain' DP was directly associated with increased 10-y ASCVD risk. Conclusions: Adherence to 'mixed' and 'rice, pasta, meat, and fish' DPs appears to reduce predicted 10-y ASCVD risk in adults in urban Ghana. Further investigations are needed to understand the underlying contextual-level mechanisms that influence dietary habits and to support context-specific dietary recommendations for CVD prevention among sub-Saharan African populations.